2008
DOI: 10.2174/156720108783331032
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Evaluation of Flurbiprofen Microemulsion

Abstract: The purpose of the present study was to investigate the microemulsion formulations for topical delivery of Flurbiprofen (FP) in order to by pass its gastrointestinal adverse effects. The pseudoternary phase diagrams were developed and various microemulsion formulations were prepared using Isopropyl Myristate (IPM), Ethyl Oleate (EO) as oils, Aerosol OT as surfactant and Sorbitan Monooleate as cosurfactant. The transdermal permeability of flurbiprofen from microemulsions containing IPM and EO as two different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…In studies conducted by Erhart LM et al, Jadhav UM et al, vivax was the most common species while Bashawri LAM et al reported higher falciparum prevalence. 3,16,17 In India, vivax is the most common species encountered followed by falciparum. However, in recent years there has been an upswing in the falciparum cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies conducted by Erhart LM et al, Jadhav UM et al, vivax was the most common species while Bashawri LAM et al reported higher falciparum prevalence. 3,16,17 In India, vivax is the most common species encountered followed by falciparum. However, in recent years there has been an upswing in the falciparum cases.…”
Section: Discussionmentioning
confidence: 99%
“…3,16,17 Thrombocytopenia is a common finding in cases of malaria both vivax and falciparum as shown by most of the studies conducted. In the present study thrombocytopenia was seen in 71% of all malaria cases.…”
Section: Studiesmentioning
confidence: 99%
“…Several formulation strategies have been reported to improve the solubility and dissolution rate of flurbiprofen, such as dry elixir (Kim and Yoon, 1995), solid dispersion (Habib et al, 1998;Oh et al, 2011), salt formation (Gupta et al, 1997), microemulsion (Park et al, 1997;Ambade et al, 2008), inclusion complex with cyclodextrins (Tokumura et al, 2009;Li et al, 2010) and cycloamyloses (Baek et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The predictors used by FRS were participant's age, systolic BP, use of antihypertensive treatment, smoking, diabetes mellitus, total cholesterol, and HDL. [15,16] This generates 2 outcomes namely, Hard CVD risk (coronary death, myocardial infarction, and stroke) and General CVD risk (coronary death, myocardial infarction, coronary insufficiency, angina, ischemic stroke, haemorrhagic stroke, transient ischemic attack, peripheral artery disease, heart failure). [22,23] Statistical analysis Numerical data was tested for normality using Kolmogorov-Smirnov test, and between groups comparison was done using either one-way analysis of variance-ANOVA (if normally distributed) or KruskalWallis test (if not normally distributed) with post-hoc tests.…”
Section: Cardiovascular Risk Calculationmentioning
confidence: 99%
“…[13][14][15] Identification of subclinical atherosclerosis and early treatment initiation has beneficial impact on cardiovascular morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%